A new species of Chlorita (Hemiptera: Cicadellidae: Typhlocybinae) from southern Italy, with redescription of C. antoniana Dlabola, 1959 - Poggi, Francesco (Zootaxa, 2025)
The leafhopper species Chlorita antoniana Dlabola, 1959, endemic to Basilicata and Calabria regions (southern Italy), is redescribed based on new findings and the study of typical and topotypical material; new diagnostic characters, not reported in the original description, are illustrated. Chlorita elvirae sp.nov. is described from Calabria region. Both taxa are monophagous on Artemisia campestris subsp. variabilis. Distribution, biology and habitat data are provided for both species.